Innovation in Management Marketing and Keeping Business Relevant in the Digital Age - Replita, Replita; Ammar, Ammar; Rasyid, Rasyid (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2023)
Research Objective on innovation in marketing management: Maintain corporate spirit in the digital age by increasing the company's online presence: In the digital age, an online business presence is essential to reach potential customers. Innovations in marketing management can help businesses improve their online presence and reach a wider audience. Increase customer loyalty: In the digital age, customers have a wealth of information and choices. Therefore, it is important to increase customer loyalty and make the brand or product relevant to them. Innovations in marketing management can help create a more engaging customer experience and interaction with a brand or product. Optimizing the use of technology: Innovations in marketing management can also help companies optimize the use of technology available in the digital age. This includes using social media, data analytics, and other technologies to improve marketing efficiency and achieve better results. Increase company competitiveness: Innovations in marketing management can help companies stay competitive in the rapidly changing digital era. By continuously developing innovative marketing strategies, companies can stay relevant and keep up with changing market trends. Increase cost efficiency: Innovations in marketing management can help companies save on marketing costs and better achieve marketing goals.